Quality of life and parental styles assessed by adolescents suffering from inflammatory bowel diseases and their parents - Jelenova, Daniela; Prasko, Jan; Ociskova, Marie; Latalova, Klara; Karaskova, Eva; Hruby, Radovan; Kamaradova, Dana; Mihal, Vladimir (Neuropsychiatric disease and treatment, 2016)
BACKGROUND: Inflammatory bowel diseases (IBDs) in adolescents are chronic medical conditions with a substantial influence on the quality of life (QoL) of the families. METHODS: A total of 27 adolescents suffering from IBD, 39 healthy adolescents, and their parents were included in the cross-sectional study. The adolescents completed the questionnaires ADOR (parenting styles), KidScreen-10 (QoL), SAD (The Scale of Anxiety in Children), and CDI (Children's Depression Inventory). The parents completed the BAI (Beck Anxiety Inventory), BDI-II (Beck Depression Inventory, second version), and PedsQL (Pediatrics Quality of Life) Family Impact Module. RESULTS: The parental styles of the parents of the IBD adolescents and controls were without significant differences. The only exception was that fathers' positive parental style was significantly higher in the fathers of the controls. There were no statistically significant differences between the IBD children and controls in the QoL assessed using KidScreen-10. However, the QoL of the parents of the ill children was significantly lower than that of the parents of the controls (PedsQL total scores in mothers 66.84±14.78 vs 76.17±14.65 and in fathers 68.86±16.35 vs 81.74±12.89, respectively). The mothers of the IBD adolescents were significantly more anxious (BAI scores 9.50±10.38 vs 5.26±4.75) and the fathers more depressed (BDI-II scores 7.23±6.50 vs 3.64±3.51) than the parents of the controls, but there was no difference in the levels of anxiety or depression between the IBD adolescents and the controls. The positive parental style of both the parents of the children suffering from IBD positively correlated with the QoL of the adolescents evaluated by KidScreen-10. The positive parental style of the fathers negatively correlated with the children's state and trait anxiety and negatively correlated with the severity of childhood depression. CONCLUSION: The fathers of the IBD adolescents may exhibit low levels of positive parenting style and be mildly depressed, and the mothers tend to exhibit higher levels of anxiety.
Keywords: quality of life; parenting style; ulcerative colitis; anxiety; depression; Crohn’s disease